Control of the nanostructure in percolative multiferroic composites on the dielectric loss and magnetism threshold. Issue 35 (21st September 2015) - Tang, Yu; Zhang, Yi; Ma, Ning; Du, Piyi
<x xml:space="preserve">Abstract</x> The nanostructure in multiferroic composites reduces the dielectric loss and shifts the magnetic threshold from a topological one.